Drivers of Mangrove Litterfall within a Karstic Region Affected by Frequent Hurricanes. (20th September 2012) - Adame, Maria F.; Zaldívar‐Jimenez, Arturo; Teutli, Claudia; Caamal, Juan P.; Andueza, María T.; López‐Adame, Haydée; Cano, Romel; Hernández‐Arana, Héctor A.; Torres‐Lara, Ricardo; Herrera‐Silveira, Jorge A.
Abstract: Tropical storms can shape the structure and productivity of mangrove forests. In this study, we compared current litterfall with historical tropical storm disturbance in the karstic Yucatan Peninsula (YP). We also explored the relationship between litterfall and the fresh/seawater mixture of floodwater. Our hypotheses were that litterfall peaks at moderate perturbations and in sites where seawater dominates the floodwater mixture, and thus, where soil total phosphorus (TP) is relatively high. Litterfall was sampled for 2 yr, from eight mangrove forests around the YP. At each site, forest structure, interstitial salinity, TP, nitrogen, carbon, pH, and bulk density were measured. Our results show that mangrove forest from northeast YP are historically impacted by stronger and more frequent tropical storms compared with those in northwest and southeast YP, where tropical storm intensity is moderate and mild, respectively. Litterfall was higher in northwest YP (≥3 g/m 2  d) compared with northeast and southeast (≤ 2 g/m 2  d), mimicking a subsidy‐stress gradient where highest productivity is reached at moderate perturbations. Neither salinity nor forest structure alone satisfactorily explained litterfall variability. Soil TP followed a similar geographical pattern as the disturbance gradient: highest concentrations in the northwest YP (≥0.05%) and lowest in the northeast and southeast (≤ 0.03%). Thus, it is likely that TP, and not tropical storm disturbance, is the main driver of litterfall in mangrove forests of the YP. Alterations in TP availability ( e.g., sea level rise and aquifer contamination) have the potential to modify mangrove productivity in the region.